Modern Icons: Aura and Memory in Super 8 Still Frames. (2nd April 2016) - Charleson, Diane
Abstract : This is an artistic practice-led article based on a set of the author's own images that have been created from found Super 8 home movies. In this article the unique properties of this medium are examined and the author's work is investigated in relation to other artists who work with Super 8. Much has been written about the role of photographs in eliciting memories. Psychological theory is here used to contend that the still framing of Super 8 home movies can provide a very potent medium for memory elicitation and sharing. According to the author, this is due to the aura – an effect created as a result of the physical properties of the images themselves, and particularly by the overexposure of light – that these images emanate. The nostalgic value of their content is also accentuated by the impact of the act of still framing. The author concludes that this experience is heightened if the images are viewed in an immersive environment – an environment that allows the viewer to be fully absorbed with the images undistracted by extraneous distractions, such as a small darkened gallery space. Such immersion fosters the possibility of a visceral experience for the viewer that promotes and allows for deep reflection and contemplation.